2012
DOI: 10.1111/j.1477-2574.2011.00398.x
|View full text |Cite
|
Sign up to set email alerts
|

Vascular architecture in anomalous right-sided ligamentum teres: three-dimensional analyses in 35 patients

Abstract: Although the right-sided components of the livers are well developed as a result of the right-dominant distribution of the feeding vessels in livers with RSLT, the basic segmental structure defined by the four sectors and the three hepatic veins are as well preserved as those in the typical liver anatomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
53
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(57 citation statements)
references
References 17 publications
3
53
1
Order By: Relevance
“…previously reported that the symmetrical configuration of the portal/hepatic venous systems and the segmental anatomy seen in the early stages of hepatic development are well preserved in adult livers with RSLT, as they are in normal livers 1, 5. (Fig.…”
Section: Introductionmentioning
confidence: 70%
See 4 more Smart Citations
“…previously reported that the symmetrical configuration of the portal/hepatic venous systems and the segmental anatomy seen in the early stages of hepatic development are well preserved in adult livers with RSLT, as they are in normal livers 1, 5. (Fig.…”
Section: Introductionmentioning
confidence: 70%
“…RSLT was suspected when one of the following findings was encountered during the initial CT screening: a strong deviation of the umbilical portion towards the right, a lack of liver parenchyma between the gallbladder and the umbilical portion, or a deeply fissured groove for the ligamentum venosum near the level of the portal bifurcation 1 . Then, the three-dimensional (3D) portal-hepatic venous relationship was examined using CT, 3D-CT, and magnetic resonance imaging (MRI) to obtain a definitive diagnosis of RSLT, as described previously 1, 11. First, the right lateral portal pedicle (Sg.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations